2011
DOI: 10.1161/atvbaha.111.232066
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-758 Regulates Cholesterol Efflux Through Posttranscriptional Repression of ATP-Binding Cassette Transporter A1

Abstract: Objective The ATP-binding cassette transporter A1 (ABCA1) is a major regulator of macrophage cholesterol efflux and protects cells from excess intracellular cholesterol accumulation, however the mechanism involved in posttranscriptional regulation of ABCA1 is poorly understood. We previously showed miR-33 was one regulator. Here we investigated the potential contribution of other microRNAs (miRNAs) to post-transcriptionally regulate ABCA1 and macrophage cholesterol efflux. Methods and Results We performed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
158
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(167 citation statements)
references
References 39 publications
(47 reference statements)
6
158
0
3
Order By: Relevance
“…This represents the fi rst such example of a transcription by guest, on May 12, 2018 www.jlr.org Downloaded from reported to repress this pathway, including miR-26, miR-106b, and miR-758 (40)(41)(42). Like miR-33, miR-758 is expressed in macrophages and its expression is downregulated in the setting of excess cholesterol ( 41 ). Overexpression of miR-758 reduces cellular ABCA1 and cholesterol effl ux, and conversely, its inhibition increases this pathway.…”
Section: Mir-33: a Master Regulator Of Lipid Metabolismmentioning
confidence: 84%
See 3 more Smart Citations
“…This represents the fi rst such example of a transcription by guest, on May 12, 2018 www.jlr.org Downloaded from reported to repress this pathway, including miR-26, miR-106b, and miR-758 (40)(41)(42). Like miR-33, miR-758 is expressed in macrophages and its expression is downregulated in the setting of excess cholesterol ( 41 ). Overexpression of miR-758 reduces cellular ABCA1 and cholesterol effl ux, and conversely, its inhibition increases this pathway.…”
Section: Mir-33: a Master Regulator Of Lipid Metabolismmentioning
confidence: 84%
“…Overexpression of miR-758 reduces cellular ABCA1 and cholesterol effl ux, and conversely, its inhibition increases this pathway. However, despite targeting distinct sites in the 3 ′ UTR of ABCA1, the effects of miR-758 and miR-33 inhibitors are not additive ( 41 ). Interestingly, miR-758 is enriched in the brain ( Fig.…”
Section: Mir-33: a Master Regulator Of Lipid Metabolismmentioning
confidence: 96%
See 2 more Smart Citations
“…miRNAs are a class of small (19-23 nt) noncoding RNAs that bind to the 3 ′ untranslated regions (3 ′ UTRs) of target mRNAs promoting degradation and/or translational repression by forming incomplete base pairing with its target mRNA (7)(8)(9). Recently, we and others have shown that ABCA1 expression is regulated by several miRNAs including miR-33, miR-758, miR-106b, and miR-144, thus revealing a novel layer of regulation of cholesterol homeostasis (10)(11)(12)(13)(14)(15)(16).…”
Section: Western Blot Analysismentioning
confidence: 99%